ﺟﺮﺍءﺍﺕ ﺗﺄﺳﻴﺲ ﺍﻟﺸﺮﻛﺎﺕ ﺍﻟﺘﺠﺎﺭﻳﺔ ﺇﺟﺮﺍءﺍﺕ ﺗﺄﺳﻴﺲ ﺍﻟﺸﺮﻛﺎﺕ ﺍﻟﺘﺠﺎﺭﻳﺔ ﺇﺟﺮﺍءﺍﺕ ﺗﺄﺳﻴﺲ ﺍﻟﺸﺮﻛﺎﺕ ﺍﻟﺘﺠﺎﺭﻳﺔ ﺇﺟﺮﺍءﺍﺕ ﺗﺄﺳﻴﺲ ﺍﻟﺸﺮﻛﺎﺕ ﺍﻟﺘﺠﺎﺭﻳﺔ - لعوﻓــﻲ، ﻴﺎﺴﻤﻴﻨﺔ; ﻤﺴﻐوﻨـﻲ ،وﻓــــﺎء (جامعة الوادي, 2024)
ﺸرﻜﺎت أﺸﺨﺎص ﺘﻘوم ﻋﻠﻰ اﻻﻋﺘﺒﺎر اﻝﺸﺨﺼﻲ، وﺸرﻜﺎت ﺘﻨﻘﺴم اﻝﺸرﻜﺎت اﻝﺘﺠﺎر أﻤوال ﺘﻘوم ﻋﻠﻰ اﻻﻋﺘﺒﺎر اﻝﻤﺎﻝﻲ، وﺸرﻜﺎت ﻤﺨﺘﻠطﺔ ﺘﻘوم ﻋﻠﻰ اﻻﻋﺘﺒﺎرﻴن اﻝﺸﺨﺼﻲ واﻝﻤﺎﻝﻲ . رﻜﺔ الﻫو ﻋﻘد رﻀﺎﺌﻲ ﻴﻠزم ﻻﻨﻌﻘﺎدﻩ أرﻜﺎن ﻤوﻀوﻋﻴﺔ ﻋﺎﻤﺔ ﻫﻲ ﻋﻘد اﻝﺸ :اﻝرﻀﺎ، اﻷﻫﻠﻴﺔ، اﻝﻤﺤل واﻝﺴﺒب، وأرﻜﺎن ﻤوﻀوﻋﻴﺔ ﺨﺎﺼﺔ ﻫﻲ :ﺘﻌدد اﻝﺸرﻜﺎء، ﺘﻘدﻴم اﻝﺤﺼص، ﺘﻘﺎﺴم اﻷرﺒﺎح واﻝﺨﺴﺎﺌر وﻨﻴﺔ اﻻﺸﺘارك .وﻫو ﻋﻘد ﺸﻜﻠﻲ ﻴﺨﻀﻊ ﻷرﻜﺎن ﺸﻜﻠﻴﺔ ﻫﻲ :اﻝﻜﺘﺎﺒﺔ اﻝرﺴﻤﻴﺔ، اﻝﻨﺸر واﻝﻘﻴد ﻓﻲ اﻝﺴﺠل اﻝﺘﺠﺎري . ءات ﺘﺄﺴﻴس اﻝﺸرﻜﺎت اﻝﺘﺠﺎرﻴﺔ ﺠازء ﻤﺘﻤﺜل ﻓﻲ اﻝﺒطﻼن وﻫو ﻴﺘرﺘب ﻋﻠﻰ ﻤﺨﺎﻝﻔﺔ إﺠار ﺜﻼﺜﺔ أﻨواع :ﺘب ﻋن ﺘﺨﻠف أﺤد اﻷرﻜﺎن اﻝﻤوﻀوﻋﻴﺔ ﻝﻌﻘد اﻝﺸرﻜﺔ، وﺒطﻼن اﻝﺒطﻼن اﻝﻤطﻠق ﻴﺘر ﻨﺴﺒﻲ ﻨﺎﺘﺞ ﻋن ﺘﺨﻠف أﺤد ﺸروط ﺼﺤﺔ اﻝﻌﻘد، وﺒطﻼن ﻤن ﻨوع ﺨﺎص ﻴﻨﺘﺞ ﻋن ﺘﺨﻠف أﺤد اﻝﺸروط اﻝﺸﻜﻠﻴﺔ ﻝﻠﻌﻘد، ﻜﻤﺎ ﺘﻨﺘﺞ اﻝﺸرﻜﺔ اﻝﻔﻌﻠﻴﺔ ﻓﻲ اﻝﻔﺘرة اﻝﻤﻤﺘدة ﻤن إﺒارم ﻋﻘد اﻝﺸرﻜﺔ إﻝﻰ ﻏﺎﻴﺔ طﻠب إﺒطﺎﻝﻪ. ﻤﺨﺎﻝﻔﺔ إﺠارءات اﻝﺘﺄﺴﻴس اﻝﻤﺴؤوﻝﻴﺔ اﻝﺠازﺌﻴﺔ وﻫﻲ ﻨوﻋﻴن ﻜﻤﺎ ﻴﺘرﺘب أﻴﻀﺎ ﻋن :ﻤﺴؤوﻝﻴﺔ ﺠازﺌﻴﺔ ﺘﻀﻤﻨﻬﺎ اﻝﻘﺎﻨون اﻝﺘﺠﺎري وﻫﻲ ﺨﺎﺼﺔ ﺒﺎﻝﺸرﻜﺎت ذات اﻝﻤﺴؤوﻝﻴﺔ اﻝﻤﺤدودة وﺸرﻜﺎت اﻝﻤﺴﺎﻫﻤﺔ، وﻤﺴؤوﻝﻴﺔ ﺠازﺌﻴﺔ ﺘﻀﻤﻨﻬﺎ ﻗﺎﻨون اﻝﻌﻘوﺒﺎت وﻫﻲ ﺨﺎﺼﺔ ﺒﺠرﻴﻤﺔ اﻝﺘزوﻴر وﺠرﻴﻤﺔ ﺨﻴﺎﻨﺔ اﻷﻤﺎﻨﺔ وﺠرﻴﻤﺔ اﻨﺘﺤﺎل ﺸﺨﺼﻴﺔ Commercial companies are divided into personal companies based on personal consideration, capital companies based on financial consideration, and mixed companies based on both personal and financial considerations. A company contract is a consensual contract that requires general objective elements for its conclusion: consent, capacity, subject matter and reason, and specific objective elements: multiple partners, providing shares, sharing profits and losses, and intention to participate. It is a formal contract subject to formal elements: official writing, publication, and registration in the commercial register. Violation of the procedures for establishing commercial companies results in a penalty represented by nullity, which is of three types: absolute nullity resulting from the absence of one of the objective pillars of the company contract, relative nullity resulting from the absence of one of the conditions for the validity of the contract, and a special type of nullity resulting from the absence of one of the formal conditions of the contract, The actual company also produces in the periodextending from the conclusion of the company contract until the request to nullify it. Violation of the procedures for establishing also results in penal liability, which is of two types: penal liability included in the commercial law and is specific to limited liability companies and joint stock companies, and penal liability included in the penal code and is specific to the crime of forgery, the crime of breach of trust, and the crime of impersonation.